Sharp Power Mean Bounds for Sándor Mean. (15th January 2015) - Chu, Yu-Ming; Yang, Zhen-Hang; Wu, Li-Min
Abstract : We prove that the double inequalityM p ( a, b ) < X ( a, b ) < M q ( a, b ) holds for alla, b > 0 witha ≠ b if and only ifp ≤ 1 / 3 andq ≥ l o g 2 / ( 1 + l o g 2 ) = 0.4093 …, whereX ( a, b ) andM r ( a, b ) are the Sándor andr th power means ofa andb, respectively.